'In Examining Others We Know Ourselves': Joanna Baillie on Sympathetic Curiosity, Moral Education, and Drama - Lauren Kopajtic (Journal of Modern Philosophy, 2024)
This paper argues that Joanna Baillie’s ‘Introductory Discourse’ to her Plays on Passions offers a theory of moral education based on an epistemology of passion—an account of how we come to know and understand the passions—both of which deserve further philosophical attention. Like her fellow Scots, David Hume and Adam Smith, Baillie offers a sentimentalist approach to human psychology, focusing on affective states as the primary constituents of character and determinants of action. She also shares a spectatorial approach to moral judgment, emphasizing the universal psychological propensity of ‘sympathetick curiosity’, which attracts spectators to those around them. I show that Baillie conceives of sympathetic curiosity in epistemic terms, as our desire to observe and know the feelings of others, claiming that ‘in examining others, we know ourselves’ (ID 74). However, for this propensity to serve properly in this role, it must be regulated through careful deployment and systematic reflection on one’s observations. I then examine Baillie’s theory of moral education through literature, showing that while Baillie sees many species of moral writing as having the function of assisting and regulating sympathetic curiosity, she privileges drama. I conclude by showing that although Baillie overstates her case in some respects, the core of her argument for the moral educational role of literature is persuasive and provides a rich resource in our study of eighteenth-century treatments of passion, character, and moral education.